Invasive Aspergillosis in a Patient With Diabetes Mellitus as the Only Risk Factor: Case Report and Literature Review - Liliana Fernández-Trujillo MD; Isabel Eraso MD; Eliana I. Morales MD; Luz F. Sua MD, PhD (SAGE Publishing, 2023)
Infection by Aspergillus covers a broad clinical spectrum, including invasive pulmonary aspergillosis (IPA) and its disseminated extrapulmonary form, invasive aspergillosis (IA). It typically occurs in severely immunocompromised hosts, but it sometimes affects the immunocompetent population, especially patients with acute diseases being treated at the intensive care unit (ICU) and less often those with chronic conditions. In this article, we report the case of a 50-year-old male, with diabetes mellitus (DM) as the only risk factor, treated for IPA and IA with cardiac and central nervous system (CNS) involvement at a high complexity institution in Cali-Colombia. Clinical presentation and radiological findings are unspecific and require a high level of suspicion. To confirm the case, histological or cytological of the fungus is required; histopathological examination of lung tissue is the gold standard, but it is difficult to perform due to respiratory compromise and high risk of bleeding, so bronchoscopy and bronchoalveolar lavage (BAL) plays an essential role in the diagnostic process. A diagnostic algorithm that includes risk assessment, symptoms, imaging findings, and isolation in cultures is essential to allow the diagnosis and initiation of treatment promptly, which includes a combination of surgery and antifungal medications for long periods, even life-long treatment.